Talent Management in the Era of Digital Globalization: Building Excellent and Adaptive Human Resources Amid Technological Change - Gita Damayanti; Sri Hartono (Oikonomia : Journal of Management Economics and Accounting, 2025)
Digital globalization has reshaped talent management practices by increasing the demand for organizations to develop highly capable and adaptive human resources. This transformation is driven by rapid technological advancements, evolving digital competencies, and intensified global competition. This study aims to analyze strategic approaches to talent management that align with the challenges of the digital era. The research employs a Systematic Literature Review based on the guidelines of Xiao and Watson and Snyder, following identification, screening, eligibility assessment, and synthesis of 21 selected articles. The findings indicate that the integration of digital technologies strengthens talent management processes by enhancing recruitment efficiency, competency development, and talent retention through artificial intelligence, data analytics, and digital learning systems. The discussion emphasizes the importance of transformative leadership, adaptive learning ecosystems, and organizational culture alignment in ensuring effective digital talent strategies. The study concludes that a comprehensive and digitally oriented talent management model is essential for building competitive and future-ready human resources. This research provides theoretical contributions to the conceptualization of digital talent management and offers structural recommendations for improving digital infrastructure and adaptive workforce capabilities.